(untitled) (Bangladesh Journal of Botany, 2020)
The quantity of antioxidant, flavanols, flavonoids, polyphenols, and catechins biochemical compounds varies among the clones and varieties. Biochemical parameters of green leaves and made tea were analyzed with standard methods using UV-visible spectrophotometer. Different biochemical and quality parameters varied markedly (p < 0.05) among the test clones. Moisture per cent (3.0 and 2.73), polyphenol (78.52 and 84.44 ppm), caffeine (68.28 and 70.3 ppm), antioxidant activity (96.4 and 97.39), theaflavin and thearubigin (ratio of TF and TR conc.; 9.99 and 9.99) contents were optimum in BT2 and BT4 clones.